2013
DOI: 10.1111/chf.12037
|View full text |Cite
|
Sign up to set email alerts
|

Thiamine Supplementation for the Treatment of Heart Failure: A Review of the Literature

Abstract: A systematic review of the literature was performed by searching Pubmed and EMBASE databases using the terms “thiamine,” “vitamin B1,” “heart failure,” “systolic dysfunction,” “ventricular dysfunction,” “cardiomyopathy,” “ventricular failure,” and “systolic failure.” Relevant trials and articles were evaluated pertaining to thiamine deficiency in patients with heart failure (HF) and references were searched for further inclusion of articles. A total of 20 articles were reviewed and summarized in detail. While … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 28 publications
0
66
0
3
Order By: Relevance
“…Inadequate ATP production in cardiac tissue can lead to release of adenosine into the plasma. Adenosine causes peripheral vasodilatation, elevated cardiac output, decreased cardiac contractility, dysrhythmias, and low diastolic blood pressure 37‐39 …”
Section: Pathophysiology Of Refeeding Syndromementioning
confidence: 99%
“…Inadequate ATP production in cardiac tissue can lead to release of adenosine into the plasma. Adenosine causes peripheral vasodilatation, elevated cardiac output, decreased cardiac contractility, dysrhythmias, and low diastolic blood pressure 37‐39 …”
Section: Pathophysiology Of Refeeding Syndromementioning
confidence: 99%
“…By preventing cardiomyocyte apoptosis, myocardial fibrosis and microvascular rarefaction in diabetic experimental hearts, benfotiamine improved their ventricular performance [16]. Other studies documented an improvement of left ventricular systolic performance in clinical and experimental models of heart failure after benfotiamine administration, whereas the drug had no effect in healthy hearts [16,17]. Benfotiamine, a transketolase activator, directing glucose to the pentose phosphate pathway, improves experimentally, the functional recovery of infarcted murine hearts, by activation of pro-survival G6PD/Akt signalling pathway and modulation of neurohormonal response [18].…”
Section: Resultsmentioning
confidence: 99%
“…Thiamin deficiency appears to be common in patients with heart failure, and supplementation has been shown to improve cardiac function, urinary output, weight loss and signs and symptoms. Therefore, this simple therapy should be tested in large scale randomized clinical trials to further determine the effects of thiamin in heart failure patients (25).…”
Section: Resultsmentioning
confidence: 99%
“…A systematic review of the literature found 20 articles, revealing evidence that supplementing heart failure with thiamine has the potential to improve left ventricular ejection fraction. Thiamin deficiency appears to be not uncommon in patients with heart failure (25) …”
Section: The Role Of Malnutritionmentioning
confidence: 99%